Conveying Complexity in Contemporary Academic Library Service Models - Sobol, Barbara (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2020)
This article will provide both practical and critical insights into contemporary library service practices using the UBC Okanagan service model redesign as a case study. In 2018 the service desk at UBC Okanagan Library was redesigned into a service zone with a fundamental goal of increasing the prominence of complex library services. By improving the visibility of research support within a newly conceptualized service zone, we addressed inclusivity through design and staffing practices while facilitating campus engagement through programming. This article offers a contribution to the ongoing discussion of consolidated service models and challenges the profession to continue experimenting with service model design and delivery in order to support diverse library patrons in an increasingly neoliberal university environment.